Rapid detection of porcine and bovine gelatin in dental prophylaxis pastes using fourir transform infrared spectroscopy - Tajudin, Noor Ashikin; Abd Aziz, Nur Fatin; Lestari, Widya; Ardini, Yunita Dewi (2015)
Aims: To detect the presence of porcine or bovine gelatins in dental prophylaxis pastes used in Malaysia by using Fourier Transform Infrared Spectroscopy (FTIR). Materials and Methods: Four brands of commonly used dental prophylaxis paste in Malaysia were collected and labelled A, B, C, and D. Pure porcine and bovine skin gelatins were used as controls. Gelatin extraction was carried out using acetone precipitation method. The extracts were then placed in the FTIR Perkin Elmer spectrometer for less than 5 minutes. All spectra were recorded within 4000– 400 cm-1 wavenumber with 4 cm-1 resolution under 40 scans. The results were analyzed by comparing the samples’ spectra with the controls’. The data were subjected to discriminant analysis using The SpectrumTM Software. Results: Sample A and porcine gelatin spectra had similar peak at 2163 cm-1 while sample B showed similarity to bovine gelatin at the range of 4000 – 2000 cm-1. Detailed analysis of the spectrum patterns of sample C in the area between 1600-1400 cm-1 and 3600-2800 cm-1 indicated an appearance of similar peaks to porcine gelatin. On the other hand, the spectrum of sample D at the range of 1800-1200 cm-1 is similar to that of bovine gelatin. Conclusions: FTIR spectroscopy was proven to rapidly detect the presence of porcine and bovine gelatins in dental prophylaxis paste and it was found that, sample A and sample C contains porcine gelatins while sample B and sample D contains bovine gelatins.